Developing a Hostel Room Swap Management System - (Case Study of Bayero University Kano) - Kabiru, Umar; Muttaka, Hafsat; Abdulhamid Said, Ahmad; Kabir Uar, Aisha (FUDMA Journal of Sciences, 2026)
In some Nigerian universities such as Bayero university Kano the current systems of swapping hostel rooms are uncoordinated and inefficient. Students often faced several challenges such as difficulty in finding other students who are willing to swap rooms, time wasted in searching manually through word of mouth or hostel posters. This paper presents a hostel room swap management system that enables students to exchange hostel rooms conveniently based on their preferences by automating and streamlining the process of requesting and approving room swaps. The system is developed using the python flask framework, HTML, CSS, Bootstrap and SQLite databases managed through SQLAlchemy. Usability evaluation was conducted using questionnaire-based approach to assess ease of use and overall user satisfaction. Overall satisfaction was notably high, with 64.5% of participants reporting they were very satisfied and 22.6% satisfied with their experience. Additionally, 90.4% of participants indicated their willingness to recommend the platform to others, underscoring its potential for wider adoption.  The results indicate positive user acceptance, demonstrating that the system effectively meets its intended objective. Future improvements should include intelligent swap matching, automated notifications, and integration of the system with the university hostel management system to enhance efficiency.
Keywords: Student Accommodation; University Hostel; Digital Solution; Swap Matching